Implementasi Moderasi Beragama Melalui Harmonisasi Agama dan Budaya di Desa Pulau Banyak - Abdurrahman, Zulkarnain; Assyauqi, Alwalid; Pratama, Zulginda; Armaya, Adelia Ayu; Athirah, Najah; Aina, Tasha; Nabila Nst, Afifah; Fikri Azkia, Muhammad Wildan; Afrillia A R, Nadia; Zaki, Muhammad Usamah (Civiliza Publishing, 2024)
Harmonization between religion and culture focuses on creating a harmonious relationship between the two in practicing religion and cultural values in the midst of a group or society. Indonesia has a variety of religions, races, tribes, customs, cultures and others that make Indonesia a country in which there are various uniqueness and relationships between differences. Pulau Banyak Village is one of the villages in Tanjung Pura District, Langkat Regency. Melayu is the majority tribe in Pulau Banyak Village and Islam is the majority religion adhered to by the people of Pulau Banyak Village. The purpose of this study was to determine the implementation of religious moderation in Pulau Banyak Village. This research uses a qualitative method, which means the research is conducted naturally and uses research procedures as they are. Pulau Banyak Village is one example of a village that implements religious moderation. Villagers often embed Islamic values in their culture so that Islam and culture become two things that are always related. For example, the making of Ashura porridge is a form of implementation of religious moderation in Pulau Banyak Village. It is also not uncommon for villagers to integrate Islamic values into cultural practices, such as wedding ceremonies, religious festivals, or cultural celebrations that are given religious meaning. Traditional Melayu clothing is also an example of the application of Islamic values in culture that maintains modesty, covers the aurat and gives an elegant and good impression in it.